2016
DOI: 10.7863/ultra.15.07041
|View full text |Cite
|
Sign up to set email alerts
|

Shear Wave Ultrasound Elastographic Evaluation of the Rotator Cuff Tendon

Abstract: Shear wave elastography shows tendon softening in rotator cuff disease. It captures information not obtained by a morphologic evaluation alone; however, a poor correlation with symptoms suggests that SWE will be less useful in workups for shoulder pain than for preoperative assessments of tendon quality. Deltoid muscle softening seen in morphologically abnormal and symptomatic patients requires further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 32 publications
(65 reference statements)
1
30
0
Order By: Relevance
“…53 USE may prove to be useful in the preoperative setting in patient selection because it can reflect tendon quality or surgical outcome. 58 In diagnosing medial epicondylitis, the addition of USE to B-mode US provides a significant improvement in the agreement between imaging and histologic results compared with either B-mode US or USE alone. 59 Furthermore, USE proved to have higher diagnostic performance compared with B-mode US.…”
Section: Tendonmentioning
confidence: 99%
“…53 USE may prove to be useful in the preoperative setting in patient selection because it can reflect tendon quality or surgical outcome. 58 In diagnosing medial epicondylitis, the addition of USE to B-mode US provides a significant improvement in the agreement between imaging and histologic results compared with either B-mode US or USE alone. 59 Furthermore, USE proved to have higher diagnostic performance compared with B-mode US.…”
Section: Tendonmentioning
confidence: 99%
“…[ 22 – 24 ] A recent US study using shear wave elastography demonstrated tendon softening in rotator cuff disorders. [ 25 ] In the present study, we targeted a population with rotator cuff tendon tears, which are common and more easily defined than other shoulder pathologies on the basis of high resolution US imaging. The prevalence of rotator cuff tendon tears in our study was 19.8%, which is similar to that observed (22.6%) in a larger cohort including 907 patients with shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally agreed that injured Achilles and rotator cuff (RTC) tendons are softer than healthy, asymptomatic tendon tissue ( Table 1 , Table 3 ) [4] , [18] , [21] , [22] , [24] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] . Of the four studies that had compared tendinopathic Achilles tendons with normal tendon using SE, pathological tendons were found to be softer than healthy tendon tissue in three studies ( n = 545 tendon thirds), whereas one study by Sconfienza et al ( n = 48) showed opposite results [4] , [29] , [31] , [40] .…”
Section: Ue Technology and Tendon-specific Basic Knowledgementioning
confidence: 99%